Major therapeutic developments and current challenges in advanced melanoma. (January 2014) - Sullivan, R.J.; Flaherty, K.T.
Summary Malignant melanoma is rising in incidence. The treatment options have been very limited but advances in molecular biology and immunology have led to a greater understanding of the pathogenesis of the disease. Four drugs have been approved for the treatment of advanced melanoma in the past 2 years and two new classes of agents have recently been shown to lead to durable responses in a substantial minority of patients. The identification of biomarkers has helped clinicians and researchers segregate patients into molecular subgroups, which facilitates the selection of therapy. Preliminary work has begun on determining the ideal sequences of the various therapies. Investigations have been carried out on why these treatments work and what the mechanisms of resistance are to these therapies. It is hoped that combinations of therapies will emerge that lead to a high percentage of durable responses.